2019
DOI: 10.1039/c9ra02473e
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of post-fermented Jing-Wei Fuzhuan brick tea alleviates liver dysfunction and intestinal microbiota dysbiosis in high fructose diet-fed mice

Abstract: Fuzhuan brick tea can improve non-alcoholic fatty liver disease (NAFLD) and intestinal microbiota imbalance induced by a high fructose diet (HFD) intake in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…The relative purity of the extracted DNA was detected by 1% agarose gel electrophoresis, and the concentration was determined using a NanoDrop 2000 UV–vis spectrophotometer (ThermoFisher Scientific, Wilmington, USA). After that, the primers 338F and 806R were used to amplify the V3-V4 region of 16S rDNA for 30 cycles with the conditions described previously . Then, the products were purified and mixed for sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative purity of the extracted DNA was detected by 1% agarose gel electrophoresis, and the concentration was determined using a NanoDrop 2000 UV–vis spectrophotometer (ThermoFisher Scientific, Wilmington, USA). After that, the primers 338F and 806R were used to amplify the V3-V4 region of 16S rDNA for 30 cycles with the conditions described previously . Then, the products were purified and mixed for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…After that, the primers 338F and 806R were used to amplify the V3-V4 region of 16S rDNA for 30 cycles with the conditions described previously. 25 Then, the products were purified and mixed for sequencing. The sequencing data were filtered, trimmed, and then used for clustering operational taxonomic units (OTU) and taxonomic analysis.…”
Section: T H Imentioning
confidence: 99%
“…21 FBT is also named Fuzhuan brick tea, Fubrick tea, Fu Zhuan tea, or Fuzhuan tea. 27,29−31 FBT has been consumed for hundreds of years in China 32 and is traditionally believed to exert preventive and therapeutic roles in obesity and metabolic disorders. 4,30 Recently, our pilot dietary intervention has proved that FBT consumption could improve blood lipids in adults.…”
Section: ■ Introductionmentioning
confidence: 99%
“…FBT is produced by the solid-state fermentation of tea leaves with probiotic Aspergillus cristatus (also named Eurotium cristatum) as the only dominant fungus. ,, This is distinguished from the other microbial-fermented teas, such as ripe Pu-erh tea, Liupao tea, and Qing brick tea . FBT is also named Fuzhuan brick tea, Fubrick tea, Fu Zhuan tea, or Fuzhuan tea. , FBT has been consumed for hundreds of years in China and is traditionally believed to exert preventive and therapeutic roles in obesity and metabolic disorders. , Recently, our pilot dietary intervention has proved that FBT consumption could improve blood lipids in adults . Moreover, it has been proved that the antiobesity effect of FBT may be associated with the modulation of gut microbiota dysbiosis. ,,, We found that the FBT aqueous extract could improve the alpha and beta diversity of gut microbiota, lower the phylum Firmicutes/Bacteroidetes (F/B) ratio, and enhance the abundance of certain beneficial bacteria belonging to the families Bifidobacteriaceae and Lachnospiraceae as well as bacteria belonging to the order Bacteroidales in high-fat diet (HFD)-fed mice. , Foster et al and Jing et al also obtained similar results in HFD-fed rats or mice.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzhuan brick tea (FT), which is prepared in the presence of a dominant fungus named Eurotium cristatum, a yellow-colored fungus and hence also known as "golden flora" in Chinese, is primarily produced in Hunan province, China. Human consumption of FT dates back to the 16th century, although recent pilot dietary interventions on humans in China have also demonstrated that consumption of FT can improve metabolic diseases (Zhang et al, 2019). It has been reported that daily consumption of FT or its extracts could alleviate obesity in both humans and experimental animals (Chen et al, 2018;Liu, 2018).…”
Section: Introductionmentioning
confidence: 99%